De peito aberto: a percepção e os sentimentos da criança cardiopata sobre o seu coração e sobre os procedimentos cirúrgicos a ele relacionados - Lembo, Cristiana Rohrs (2019)
This research aimed to investigate the perception and the feelings of the cardiac child about their hearts and their heart surgeries. The literature review prior of this study revealed a gap of the children’s point of view about this experience. Mainly studies about this population were made from the parents or the health professionals perceptions. The data was collected with a qualitative design and analyzed according to the Analytical Psychology. The participants which were studied were from the ACTC – Casa do Coração, located at São Paulo. As instruments, were used a play box and a heart drawing, made by the children. The data collected was studied in twelve analyzing categories: trauma, food cravings, toys and childplays from their hometown, violence felt at the hospital procedures, relatives that were missed, caregiver help, plans and insecurities about the future, pain, relationship with the doctor, the heart which contains, the red heart, positive transference with the researcher and the heart with a gap. It was observed that the hospital experience not only brings physical and emotional pain, but can also generate a psychic trauma. In this way, it is important for the family and the health professionals that work with this population guarantee help and caring for this children